2014
DOI: 10.12788/jcso.0094
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of resolution in navigated patients with abnormal cancer screening tests

Abstract: Background Patient navigation has been effective in improving cancer care, yet little is known about what predicts timely outcomes in navigated patients. Objective We identified predictors of resolution of abnormal cancer screening tests in patients who received navigation. Methods We examined data on patients with abnormal breast (n = 256) or cervical (n = 150) screening tests or symptoms who received navigation as part of the Ohio Patient Navigator Research Program during 2007–2010. We used multivariable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
(28 reference statements)
1
3
0
Order By: Relevance
“…The comparison of the dimension of lifestyle and stress management indicated a significant relationship between the two groups. The mean score of stress management in patients was lower compared to healthy women, which is in agreement with the result of the study by Reiter et al (35). Similarly, Oran et al discovered changes in HPLP is possible by increasing the awareness about the periodic screening of cancer, but this is not applicable to all women in the community.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The comparison of the dimension of lifestyle and stress management indicated a significant relationship between the two groups. The mean score of stress management in patients was lower compared to healthy women, which is in agreement with the result of the study by Reiter et al (35). Similarly, Oran et al discovered changes in HPLP is possible by increasing the awareness about the periodic screening of cancer, but this is not applicable to all women in the community.…”
Section: Discussionsupporting
confidence: 86%
“…However, scientists have not yet been able to explain this relationship (34). Cigarettes might be a cofactor of women's cancers, which works through thickening the cervical mucus (35). Smoking further decreases the immune response in cervical cells and may affect the metabolism of female hormones.…”
Section: Discussionmentioning
confidence: 99%
“…36 A disproportionate burden of barriers among poor and minority women contributes to delays in follow-up care. 29,38,39 Furthermore, Tejeda et al 40 found that Hispanic women reported barriers: more often than black women. 29,38,39 Furthermore, Tejeda et al 40 found that Hispanic women reported barriers: more often than black women.…”
Section: Patient Navigationmentioning
confidence: 99%
“…37 Women with barriers tend to have a longer time to diagnostic resolution of abnormal mammogram than women without barriers. 29,38,39 Furthermore, Tejeda and colleagues found that Hispanic women were more often than black women to report barriers. The authors suggest that this difference between black and Hispanic women may be associated with types of barriers, where Hispanic women compared with black women were more likely to report intrapersonal barriers such as financial problems, transportation, fear, and comorbility.…”
Section: Introductionmentioning
confidence: 99%